Neuraeschna tapajonica sp. n. da região amazônica do Brasil (Odonata: Aeshnidae) (Lundiana: International Journal of Biodiversity, 2002)
Neuraeschna tapajonica sp. n. is described and illustrated from a single male (holotype: Itaituba, Pará, Brazil). It is close to N. dentigera Martin, 1909 from which it is distinguished mainly by the structure of the superior appendages.